Resilient Organizations for River Restoration: The Case of Two Colorado River Sub-Basin Recovery Programs - Srinivasan, Jaishri; Lorenzo, Theresa E.; Schoon, Michael L.; White, Dave D. (Frontiers in Water, 2021)
This study characterizes the resilience of organizations undertaking river basin governance and recovery. The Upper Colorado River Endangered Fish Recovery Program (UCREFRP) and the Lower Colorado River Multi-Species Conservation Program (LCR-MSCP) are defined in this study as polycentric organizations nested within larger institutional mechanisms governing the Colorado River Basin. This study utilizes an environmental disturbance-organizational response framework to characterize organizational resilience – and uses attitudinal diversity (characterized by attitudes towards agendas) as the measurable metric. Environmental disturbances are defined as either press or pulse and categorized as either institutional or biophysical in nature. Four types of attitudinal diversity metrics are utilized – supportive, clarifying, conditional and critical. Results indicate that institutional press and pulse events generated anticipatory resilience capabilities along with some adaptive capabilities for the organizations. However, the biophysical press and pulse events only reveal coping capabilities and very little adaptive capabilities. With the recent Colorado River shortage declaration, it is critical for the programs to build anticipatory as well as adaptive capabilities for optimal response to biophysical press events.